1989
DOI: 10.2105/ajph.79.4.463
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of hepatitis A among illicit drug users, Oklahoma, 1984-87.

Abstract: Transmission of hepatitis A has been described in many settings, although few outbreaks have been reported among illicit drug users. We report six unrelated outbreaks of hepatitis A among users of marijuana and intravenously administered methamphetamine. Although the exact mode of transmission could not be IntroductionOutbreaks of hepatitis A infection have resulted from common-source food and water-borne transmission and from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 15 publications
0
22
0
3
Order By: Relevance
“…Outbreaks of HAV infection among injection drug users (IDUs) have been reported in North America and Scandinavia (97,101,143). Several routes of transmission are likely to occur, and these include a combination of personto-person and percutaneous spread.…”
Section: Modes Of Transmission and Sources Of Hav Infectionmentioning
confidence: 99%
“…Outbreaks of HAV infection among injection drug users (IDUs) have been reported in North America and Scandinavia (97,101,143). Several routes of transmission are likely to occur, and these include a combination of personto-person and percutaneous spread.…”
Section: Modes Of Transmission and Sources Of Hav Infectionmentioning
confidence: 99%
“…Harkess et al (1989) reported on six unrelated outbreaks of hepatitis A among users of marijuana and intravenously administered methamphetamine. Although the exact mode of transmission could not be determined, it was suggested that practices associated with illicit drug use facilitated transmission of hepatitis A.…”
Section: Marijuanamentioning
confidence: 99%
“…Early sexual behavior and frequent unprotected sex among heterosexual and homosexual users of methamphetamine result in higher rates of Hepatitis and HIV infection rates (Davis, Kalousek, & Rubenstein, 1970; Gorman, 2003; Greenwell & Brecht, 2003; Harkess, Gildon, & Istre, 1989; Hutin et al, 2000; Koester, Glanz, & Barón, 2005; Meyer, 2003; Molitor, Truax, Ruiz, & Sun, 1998; Urbina & Jones, 2004; Vogt et al, 2006). Methamphetamine use interferes with the efficacy of HIV medications and treatment (Anonymous, 2004; Boddiger, 2005; Jernigan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%